To investigate the role of additives on the flow characteristics of fly ash slurry at high concentration - Gill, Rajeev (My University, 2013)
Coal based thermal power plants all over the world face serious problems of handling and disposal of the fly ash produced. Thermal power stations use pulverized coal as fuel. They produce enormous quantitative of coal ash as a by- product of combustion. The high ash content (30-50%) of the coal in India makes this problem more complex. Transportation of fly ash is a major problem in its efficient disposal. The main problem associated with fly ash transportation is that the particles settle down sooner than desired. The primary objective of this research is that not only the fly ash particles should remain floated till it reaches the end but also settle down after that. In this investigation the role of a drag-reducing (additives) has been evaluated to achieve the objectives. The additive used are detergent Ariel which act as an anionic surfactant in nature, Glycerol and polyethylene glycol (reffered as PEG) which are act as a non-anionic surfactacts in nature and anionic sodium lauryl sulfate (reffered as SLS).The action of different these additives on flow behaviour of slurry is studied at different dosage using a rheometer.. Effect of 3 concentrations of additives (0.5%, 1% and 1.5% by weight) on viscosity of 40%, 50%, 60% and 65% fly ash slurry is studied. The effective design, control and safe operation of a slurry hydraulic transport system require the successful prediction of slurry flow behavior in the pipeline. To study the good flow behaviour is to matching the actual data with rheological models (Bingham’s model, Power law’s model and Harschel-Bulkley model) values. Slurry flow behavior is not only dependent on the properties of both solids and carrier, but also it is strongly affected by mutual particle-particle and particle liquid interaction. Rheological models are excellent mathematical tools which help to analyze good flow behaviour. Study indicates that, additives of different nature (anionic and non-ionic surfactant) help reduce viscosity and shear stress of slurry which leads to decrease in specific power consumption and increase overall the transport system efficiency. Particle size distribution plays an important role to obtain higher concentrated slurries and higher carrying capacity. In this work, the particles of different size range are extracted through mechanical sieving and flow behaviour of slurries at 53-106μm is made at different concentrations. The study relivance the large particle size adversely affects flow behavior.
Master of Engineering-Thermal, Dissertation
Keywords: rheology; fly ash